ORGANISASI SOSIAL DALA’IL KHAIRAT (Studi Pengamal Dala’il Khairat K.H Ahmad Basyir Kudus) - Abdul Jalil (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2011)
This research will try to find the influence of the spirit of Dala’il Khairat toward work ethos in improving financial of the santri (student). Moreover this research is trying to observe the processes being done by thestudent in developing business in obtaining the success. Qualitativemethod is applied through deep interview, participation observation anddocumentation in order to obtain the data in Pesantren Darul FalahJekulo Kudus, directed by KH Ahmad Basyir as Mujiz of dala’il khairat forthose students applying this practices. Economic analysis for those studentperforming dala’il khairat shows the influence of spirit or the believes ofpertaining dala’il toward business improvement. The spirit of dala’il hasbrought them to be more spirit and having higher work ethos. Additionally,this research shows a concept of the relationship of applying dala’il khairatwhich is assumed as believes that will improve their financial.